A comparison of intrathecal clonidine and buprenorphine as spinal anesthesia adjuvant for abdominal and lower limb surgeries - Mallappa, Kiran; Manjunath BN,; Narendra PL,; Kavi, Chandrashekarappa (Asian Journal of Medical Sciences, 2023)
Background: Many intrathecal adjuvants are being used with local anesthetics to prolong the intraoperative anesthesia and postoperative analgesia. Clonidine and buprenorphine are known to potentiate the effects of local anesthestics. Aims and Objectives: This study was designed to compare the duration of postoperative analgesia as well as duration of sensory and motor block onset, intraoperative hemodynamic changes, and perioperative complications between buprenorphine and clonidine when used as an adjuvant to intrathecal hyperbaric bupivacaine. Materials and Methods: A randomized double-blind study for 80 patients undergoing lower abdominal surgeries and lower limb surgeries was designed with Group B receiving 50 mcg of buprenorphine and Group C receiving 50 mcg of clonidine with 15 mg of hyperbaric bupivacaine 0.5%. Student’s t-test and Chi-square were used for comparing the data. Results: The time of onset of duration of post-operative analgesia as well as sensory and motor block was significantly higher in buprenorphine group as compared to clonidine group. In present study, incidence of bradycardia as well as hypotension was significantly higher in group C as compared to group B (P<0.05). Conclusion: Addition of intrathecal buprenorphine and clonidine potentiates the duration of analgesia, sensory and motor block, with buprenorphine has a longer analgesic effect when compared to clonidine.